The Danube Civilization and its Pivotal Role for Understanding the Formation Process of Advanced Civilizations in Antiquity - Haarmann, Harald (Zeitschrift für Balkanologie, 2025)
In this contribution, a sequence of stereotypes, clichés and traditional notions is presented that have shaped the canon of Western historiography and, accordingly, the related programmes for school education. Outdated notions such as ex oriente lux (“Light from the East”), which have dominated the academic discourse about the origins of Western civilization, are addressed here and replaced by concepts that rely on investigations and analyses derived from modern interdisciplinary research. In an overview of sixteen maxims, revisions of outdated views are presented, with the aim of creating a new paradigm of historiography, paying due tribute to the principle of ex occidente lux (“Light from the West”). A timeline, presented as an appendix, illustrates the panorama of advanced civilizations in a comparative overview.